The Influence of Managerial Ownership, Debt to Equity Ratio, and Return on Assets on Dividend Policy in Building Construction Sub-Sector Companies Listed on the Indonesia Stock Exchange - nurdina nurdina; R. Yudi Sidharta; Habibatul Ma’rufah (Universitas Islam Lamongan, 2023)
This study aims to determine the effect of managerial ownership, Debt to Equity Ratio (DER), and Return On Assets (ROA) on Dividend Policy. The population in this study is the Building Construction Sub Sector Companies listed on the Indonesia Stock Exchange, totaling 18 companies. The method of determining the sample using purposive sampling, there are 7 companies for 5 periods with a total sample of 35 data. The type of data is secondary data, namely financial reports in 2017-2021. The results of the study show that the Debt to Equity Ratio has an effect on dividend policy, while managerial ownership and Return On Assets have no effect on dividend policy..